Política agrícola e desenvolvimento da área de influência do Projeto de Integraç\~ao do S\~ao Francisco - César Nunes de Castro; Monise Terra Cerezini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– A considerable part of the population in the area of influence (AI) of the S\~ao Francisco Integration Program (PISF) in the states of Pernambuco, Paraíba, Rio Grande do Norte and Ceará survives from agricultural production in the approximately 500 thousand agricultural establishments scattered throughout the AI PISF. It is expected that the PISF, along with other public policies, will contribute to the development of this much-needed portion of the Brazilian semiarid region. The objective of this article is to analyze the implementation of some of the agricultural policies of the Federal Government in the territory composed of the 398 municipalities of the AI PISF. Special analytical emphasis is given to initiatives related to family farming, a category in which most agricultural establishments in the region are classified. In this sense, two public policies to support family farming, the National Program for Strengthening Family Agriculture (PRONAF) and the Food Acquisition Program (PAA), constitute focal points of the analysis exposed throughout the article. Among the findings of the study, special mention to the coverage of PRONAF in the region, about 99.9% of family establishments are linked to PRONAF. A segment of the agricultural sector that is constantly the target of projects and public policies in the region is irrigated agriculture. Regarding this, the data shows that the goals established by the Federal Government, around 2005, for the irrigated area in the region in 2025 are very far from being achieved. Therefore, some caution is proposed regarding the goals for the expansion of irrigated agriculture in the AI PISF.
Keywords: Q15; Q16; Q18; 330; water infrastructure; agriculture; Pronaf